Alice: Rapid prototyping system for virtual reality - Pausch, Randy; Burnette, Tommy; Capeheart, A.C.; Conway, Matthew; Cosgrove, Dennis; DeLIne, Robert; Durbin, Jim; Gossweiler, Rich; Koga, Shuichi; White, Jeff (IEEE Computer Graphics and Applications, 1995)
We are developing Alice, a rapid prototyping system for virtual reality software. Alice programs are written in an object-oriented, interpreted language which allows programmers to immediately see the effects of changes. As an Alice program executes, the author can update the current state either by interactively evaluating program code fragments, or by manipulating GUI tools. Although the system is extremely flexible at runtime, we are able to maintain high interactive frame rates (typically, 20-50 fps) by transparently decoupling simulation and rendering. We have been using Alice internally at Virginia for over two years, and we are currently porting a "desktop" version of Alice to Windows 95. We will distribute desktop Alice freely to all universities via the World Wide Web; for more information, see http://www.cs.virginia.edu/ alice/